The effect of non-pharmaceutical policy interventions on COVID-19 transmission across three cities in Colombia - Poppe, Adriana; Maskileyson, Dina (Frontiers in Public Health, 2022)
Governments across the globe have implemented different strategies to handle the COVID-19 pandemic. A national mandatory quarantine was the most applied policy tool. While there are studies that tested the effectiveness of a national mandatory quarantine, the question about the effectiveness of additional quarantine policies is not yet answered. In this study we focus on three large cities in Colombia (Bogota, Medellin and Cali) with similar socio-economic conditions but made use of different COVID-19 prevention measures. We examine whether different non-pharmaceutical policy interventions (NPIs) conducted in these three cities are effective against the spread of the COVID-19 pandemic. We inspect the effect of the quarantine policies restricting exit from home by sex, ID number, whereby only Bogota implemented the restriction to leave the home according to sex followed by a restriction according to ID number, and Medellin and Cali implemented a restriction by ID number only. Data for the analysis are obtained from the National Administrative Department of Statistics of Colombia [Departamento Administrativo Nacional de Estadística (DANE)]. The data on pandemic severity is measured by the number of confirmed COVID-19 cases per city. We conduct single-group interrupted time series analysis (ITSA) to examine differences in the extent of the pandemic severity in Bogota, Medellin and Cali. We found that NPIs in all three Colombian cities had a positive effect on slowing the spread of the pandemic.